Pathological and Ileal Microbiota Findings in Seven-Day-Old Chicks with Gizzard Lesions and Growth Delay - Dayse Helena Lages da Silva; Luana Ferreira Marques Cordeiro; Diego Lisboa Rios; Oliveiro Caetano de Freitas Neto; Leonardo José Camargos Lara; Juan Carlos Ariute Oliveira; Flávia Figueira Aburjaile; Roselene Ecco (Poultry)
Gizzard erosion and ulceration (GEU) is characterized by defects and necrosis in the koilin layer, particularly in broilers. This condition has been associated with growth retardation, runting, and economic implications for poultry producers; nevertheless, its influence on gut microbiota remains unknown. This study investigated the compositional changes in the bacterial community of the ileum of seven-day-old broiler chicks with GEU using next-generation sequencing (NGS) technology. Twenty-two samples were obtained from the ileal mucosa and contents of sixteen chicks with GEU and six without GEU raised in a conventional system located on a farm in southeast Brazil. The results revealed that bacterial phyla in both groups exhibited a similar composition, with Firmicutes representing the most abundant. Porphyromonas, Candidatus Arthromitus, and Limosilactobacillus were statistically more abundant in the group without GEU. The most prevalent genera in the group with GEU were Lactobacillus and Enterococcus, and the relative abundance of Enterococcus in the ilea of some chicks with GEU was considerable. Based on the results of the current study, necrosis in the koilin layer can change the composition of ileal microbiota. Therefore, further studies should be carried out to clarify whether GEU and consequently poor digestibility of the feed cause significant changes in the intestinal microbiota.